Zu Kasusalternationen bei der Präposition na ‚auf‘ im Polnischen und ihren deutschen Entsprechungen - Anna Pilarski (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The article is dedicated to the local preposition na ‘on’ in Polish and its German equivalents auf. The main focus of the study are case alternations associated with the use of the preposition. The locative case in Polish is regarded as a structural case. Based on the observations on verb-independent case alternations, the preposition na ‘on’ in Polish is considered as a functional category with regard to the Principles and Parameters Theory the Minimalist Program.